Prevalence and molecular characterisation of extended-spectrum Î²-lactamases genes in Escherichia coli and Salmonella spp. isolated from fish samples in Chhattisgarh, India - Khan, Rizwan; Shakya, Sanjay; Gade, Nitin Eknath; Jain, Asit; Patyal, Anil; Ali, S.L.; Chandrakar, Choodamani; Hattimare, Deeksha Deepak; Pandey, Ajeet Kumar (Indian Journal of Fisheries, 2021)
coli and Salmonella spp. Out of 200 samples collected from retail markets of Durg, Raipur, Rajnandgaon and Baloddistricts of Chhattisgarh State, 76 (38) and 46 (23%) samples were found contaminated with E. coli and Salmonella spp.,respectively. Multiple antibiotic resistant (MAR) index varied between 0.00 to 0.88 and 0.11 to 0.88 for E. coli and Salmonellaisolates, respectively. The isolates were screened phenotypically for ESBL production and multiplex PCR targeting blaTEM,blaSHV, andblaCTX-M genes, was carried out followed by sequencing. Prevalence of blaTEM, blaSHV and blaCTX-M genes in E.coli and Salmonella isolates were found to be 13.2, 1.3, 0 and 6.5, 0, 4.4%, respectively. Higher percentage of resistantgenes was detected in plasmid DNA in comparison to genomic DNA. Sequencing of PCR amplicons of blaTEM and blaCTX-Mgenes revealed the presence of blaTEM-116 and blaCTX-M-15 variants, respectively. The study indicates the presence of multidrugresistant ESBL producing E. coli and Salmonella in fish samples, which may pose threat to the fish consumers.Keywords: blaTEM, blaSHV, blaCTX-M, E. coli, Fish, MAR index, Salmonella